(The impact of work ethic on job performance (Field Study on Female Employees of King Saud University in Riyadh - Alhzaima, Ahmed bin Saleh; al - Attas, Nour bint Hassan (Journal of Economic, Administrative and Legal Sciences, 2018)
The research aimed to identify the ethics of work in their aspects (honesty، self-censorship، sincerity، proficiency، integrity and justice) their impact on job performance. A field study was conducted on the female employees at King Saud University in Riyadh. The analytical descriptive methodology was used. The performance consisted of a questionnaire containing (40) items distributed to (355) female employees. A number of results were obtained، the most important of which was the high level of work ethics for female administrative employees at King Saud University in Riyadh and obtained a general average (4.15). At the level of the mentioned aspects، (integrity، self-censorship and honesty) obtained averages (4.31، 4.24، 4.21) respectively، all of which were rated (Highly agreed) while the aspects، (loyalty، proficiency، justice) obtained averages (4.19، 4.18، 3.79) respectively، all of which were rated (agreed). The results of the study showed that the members of the study population agreed on the level of job performance. The overall general arithmetic average of the aspect rated 3.85 of 5 with (agreed) grade. There is a statistically significant direct relationship between work ethics and the level of job performance، up to 0.50. it was also found that there was an impact of the ethics of work on the performance of the female administrative employees at King Saud University in Riyadh rated (0.39) with a medium effect. The results showed that there was a statistically significant relationship according to (age، educational qualification، years of experience، and functional level) variables for whose ages are (30 to 39 years)، whose educational qualification is (bachelor)، whose years of experience are 5 – 10 years and whose functional level is (head of department). In the light of the results and then after providing a set of recommendations and proposals to develop the moral skills of female employees، improve performance and create a positive interaction environment between the female employees of the university and the general institutions.